(untitled) (Homoeopathy for All, 2025)
Gastroesophageal reflux is a normal physiologic event that may occur as often as once an hour. The causes for the transformation of this normal process into a chronic, relapsing illness have not been well defined, but numerous factors are thought to be involved. The symptoms of Gastroesophageal Reflux Disease (GERD) vary from patient to patient, and multiple diagnostic tests and treatments are available.